Hubungan Penggunaan KB Suntik dengan Perubahan Berat Badan Akseptor KB di Desa Sumberwringin Kecamatan Klakah Tahun 2022 - Putri, Nina Pratama Kurnia (NHM PRESS, 2023)
Injection contraception is a method of contraception that is given by injection. The injection method has become part of the national family planning movement and its demand is growing. The high demand for injections is because It is safe, simple, effective, does not cause interference and can be used after childbirth. The purpose of this study was to determine the relationship between the use of injectable contraceptives and changes in body weight of family planning acceptors. This observational study uses a descriptive analytical research design, namely research that explores how and why this health phenomenon occurs. Then analyze the dynamics of the correlation between phenomena or between risk factors and effect factors. Cross sectional methodology is employed. There were 32 participants in the study as a whole. Total sampling was used in this investigation, and a total of 32 participants were included in the sample. An observation sheet was employed as the method of data collecting (K4 card). Utilizing the SPSS application, statistical methodology. The findings revealed that out of 32 respondens, 21 had gained weight, 7 had a constant weight, and 4 had lost weight. The SPSS program’s statistical findings, which result in a P value <0.05 (H0 rejection), show a connection between injectable contraceptive use and changes in KB supporters’ body weight. To reduce the number of acceptors who experience weight gain by adjusting their diet and doing physical activity every day for at least 30 minutes.